Road MAP of National Development Through The V Amendment of The 1945 Constitution - Abustan, Abustan (Devotion : Journal of Research and Community Service, 2022)
The actualization of the 1945 Constitution of the Republic of Indonesia in the administration of the state, after 23 years of reform or after 4 amendments have been made, it is deemed necessary/important to carry out the 5th amendment. solely on the needs/allegances of the state and it is relevant to the affairs of the life of all Indonesian people. The research method used is normative juridical research considering that what is studied is the result of books and regulations regarding: the ratio of amendments to the 1945 Constitution of the Republic of Indonesia, public participation in constitutional changes, the national development planning system (SPPN), and reconstruction of the state policy model of the main principles of the state. . The basic question related to the current state administration issue is bringing back the State Policy Guidelines to be an important choice? In the course of Indonesia's state administration, it seems that a national development roadmap is urgently needed, in order to realize a good government, and maintain the sustainability of national development (sustainable government) so that the government (President) of the development program becomes a Vision-Mission that must be continued even though the President changes.